ENRICHING STUDENTS’ VOCABULARY ACQUISITION IN ENGLISH AS A FOREIGN LANGUAGE (EFL) THROUGH VISUAL AIDS AT MTS BABUSSALAM DDI KASSI JENEPONTO - Mutiara Resky Maya; Muh. Arief Muhsin; Uyunnasirah Hambali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether Flashcards as visual aids can enrich students' vocabulary acquisition in English as a Foreign Language (EFL). The method used is Classroom Action Research (CAR), which was implemented at Mts Babussalam DDI Kassi by involving 7th-grade students as the population and 25 students from class VII D as a sample selected by random sampling technique. The results of the study showed a significant increase in students' average scores. The score on the diagnostic test was 22.20, the cycle I test reached 56.80, and the cycle II test increased to 90.80. The implementation of the use of Flashcards in learning resulted in a significant difference in scores, namely 34.60 points from the diagnostic test to cycle I, 34.00 points from cycle I to cycle II, and 68.60 points from the diagnostic test to cycle II. These results are supported by a significance value (Sig.) of 0.000 which is smaller than 0.05. Thus, this study shows that the use of Flashcards as a learning medium can significantly enrich students' vocabulary.